POSTGRADUATE STUDIES AT THE THIRD LEVEL OF HIGHER EDUCATION: DISCURSIVE FIELD - Valery P. Shestak; Nadezhda V. Shestak (Высшее образование в России)
The paper proposes to shift the center of gravity of the development of postgraduate educational programs discussion in a social discursive field in which inconsistencies and uncertainties in the existing regulatory and legal framework of the modernization process of training and certification of highly qualified scientific personnel are brought into correlation with the main target - degree thesis preparation. The interest to the institution of postgraduate study and dissertation theses in Russian society is constantly decreasing. The results of comparing the education at graduate and postgraduate levels, as well as the existing postgraduate studies models in the world are given. The authors come to a conclusion that the social problems of post-graduate institution are much more significant than any the educational programs preparation problem.